Aborted sudden cardiac death in a young soldier with concomitant hypertrophic cardiomyopathy and Wolff–Parkinson–White syndrome. (26th December 2018) - Kim, Sunwon; Song, Woo Hyuk; Kim, Sung Soon
Abstract: We present a young soldier presenting with aborted sudden cardiac death, who was found to have concomitant hypertrophic cardiomyopathy and Wolff–Parkinson–White syndrome. Along with pathological haemodynamic features of hypertrophic cardiomyopathy, an easily-inducible re-entrant tachycardia was clearly documented in our patient. Given the fatal potential of supraventricular tachycardia in hypertrophic cardiomyopathy, we postulated that his tachyarrhythmia could potentially trigger the event. Upon his refusal to receive implantable cardioverter/defibrillator therapy, we ablated anatomical arrhythmogenic substrate instead, and he remained uneventfully over 3 years on β-blocker.